Community-acquired pneumonia caused by methicillin-resistant Staphylococcus aureus in critically-ill patients: systematic review - Nuria Carballo; Marta de Antonio-Cuscó; Daniel Echeverría-Esnal; Sonia Luque; Esther Salas; Santiago Grau (Elsevier, 2017)
Introduction: Community-acquired pneumonia (CAP) is associated with high morbidity and mortality rates. Despite methicillin-resistant Staphylococcus aureus (MRSA) having often been associated with nosocomial pneumonia, the condition of some MRSA CAP patients is severe enough to warrant their being admitted to ICU. Objective: The purpose of this study is to conduct a systematic review of the literature on antibiotic treatment of MRSA CAP in critically-ill patients. Material and methods: An online search was conducted for locating articles on MRSA CAP in critically ill patients. Relevant publications were identified in PUBMED, the BestPractice database, UpToDate database and the Cochrane Library for articles published in English within the December 2001 - April 2016 time frame. Results: A total of 70 articles were found to have been published, 13 (18.8%) having been included and 57 (81.4%) excluded. Cohort studies were predominant, having totaled 16 in number (20.7%) as compared to one sole cross-sectional study (3.5%). Conclusions: The experience in the treatment of MRSA CAP in patients requiring admission to ICU is quite limited. Vancomycin or linezolid seem to be the treatments of choice for MRSA CAP, although there not be any specific recommendation in this regard. It may be useful to use alternative routes, such as administration via aerosolized antibiotics, continuous infusion or in association with other antibiotics.